The Role of Qawā’id Fiqhiyyah in Strengthening Waqf Law: A Review of Challenges and Solutions in Indonesia - Jalili, Ismail; Firdaus, Muhammad; Fahm, AbdulGafar Olawale (Hukum Keluarga Islam IAIN LANGSA, 2024)
The article addresses the various challenges that waqf (Islamic endowment) law faces in Indonesia. It specifically investigates how the application of Qawā'id Fiqhiyyah (principles of Islamic jurisprudence) can enhance waqf law considering obstacles such as public ignorance about waqf, inadequate legal frameworks, and the necessity for effective management strategies to improve the productivity of waqf assets. The aim of this research is to analyze how Qawā’id Fiqhiyyah can provide foundational support to enhance Waqf law, proposing viable solutions to existing issues. The novelty of this research lies in its integrative approach, which combines traditional Islamic legal principles with the contemporary challenges of waqf management. By focusing on Qawā'id Fiqhiyyah, the study proposes a framework that not only addresses legal and administrative issues but also highlights the cultural and social dimensions of waqf in Indonesia, an area that has not been extensively explored in existing literature. . The results of the research suggest that the application of Qawā'id Fiqhiyyah can provide practical solutions to the identified challenges in waqf law. The study outlines several strategies, including enhancing public education about waqf, improving legal frameworks, and fostering collaboration among various stakeholders such as government bodies, religious organizations, and the community. These strategies aim to create a more effective and sustainable waqf system in Indonesia, ultimately leading to increased productivity and a greater social impact of waqf assets